High-mobility pentacene phototransistor with nanostructured SiO2 gate dielectric synthesized by sol-gel method - Okur, S.; Yakuphanoğlu, Fahrettin; Stathatos, E. (Elsevier Science Bv, 2010)
We have fabricated a pentacene based phototransistor by employing a modified nanostructured SiO2 gate dielectric. The photosensing properties of the pentacene thin film transistor fabricated on n-Si substrate with nanostructured SiO2 as gate dielectric have been investigated. The photocurrent of the transistor increases with an increase in illumination intensity. This suggests that the pentacene thin film transistor behaves as a phototransistor with p-channel characteristics. The photosensitivity and responsivity values of the transistor are 630.4 and 0.10 A/W, respectively at the off state under AM 1.5 light illumination. The field effect mobility of the pentacene phototransistor was also found to be 2.96 cm(2)/Vs. The nanostructured surface of the gate possibly is the cause of the high-mobility value of the phototransistor due to light scattering from the increased Surface area. Crown Copyright (C) 2009 Published by Elsevier B.V. All rights reserved.
Keywords: Organic semiconductor; Pentacene; Phototransistor; Nanostructured SiO2 insulating gate; Sol-gel method; Thin film phototransistor; Interface state density